Influence of Age-Related Complications on Clinical Outcome in Patients With Small Ruptured Cerebral Aneurysms - Zheng, Jianfeng; Sun, Xiaochuan; Zhang, Xiaodong (Frontiers in Neurology, 2020)
Background Small ruptured cerebral aneurysms (≤5mm) accounted for a majority of aSAH, and its clinical management remains a challenge. The aim of this study was to identify the effect of age-related complications on the outcome of small ruptured aneurysms patients. Methods A retrospective review was performed in small ruptured aneurysms patients who underwent microsurgical clipping or endovascular coiling from September 2012 to December 2018. According to the age, patients were divided into the elderly group and the non-elderly group. Baseline characteristics, clinical complications and outcome of patients were analyzed between the two groups. Multivariate logistic regression analysis was used to determine the risk factors associated with poor outcome of elderly patients. Results In the elderly group, 83 patients treated with clipping, and 50 with coiling. In the non-elderly group, 188 patients treated with clipping, and 117 with coiling. The incidence of neurological complications with neurologic deficit in the elderly group was significantly higher compared with non-elderly group (P = 0.006). Elderly patients had longer hospital stay (P = 0.032) and poorer outcome (P = 0.001) compared with non-elderly patients. Multivariate analysis showed that irregular aneurysms (P = 0.045) and ischemic events (P < 0.001) were independent risk factors associated with poor outcome in elderly. Conclusions Neurological complications with neurologic deficit, especially ischemic complications, were clearly more common in the elderly patients. Irregular small aneurysms or postoperative ischemic events should be paid attention as the higher risk of poor outcome in elderly.